Disruptions in Lifestyle Due to Escalating Screen Time: A Behavioural Perspective - Gupta, Roshani; Vatta, Lalita (Indian Journal of Extension Education, 2025)
Heavy reliance on screen media can negatively affect the daily lives and activities of adolescents and youth. The study aims to find out the association between increased screen time and its impact on lifestyle among adolescents and youth. Cross-sectional descriptive research was conducted for this purpose between March and August of 2023. The stratified random sampling method was used to select 200 participants from the age group of 14-18 years. After getting a permission letter from the District Inspector Officer of Schools (DIOS), participants were approached from various selected schools in Varanasi District, Uttar Pradesh. In this study, a self-structured questionnaire with twenty-two closed-ended questions was included. The study findings highlighted that increased screen time was found to be negatively associated with outdoor activities, backlogs from household activities, and the inability to draw attention from the screen. The results also indicated that there were no distinct gender differences in the tendency to continue using screens after using them and that screen use was higher on weekends than on weekdays.